The incumbent's deep tech strategy playbook : by taking a three-step approach to engaging with deep-tech ecosystems, incumbent companies can remain competitive, drive innovation, and create commercially valuable offerings - Candelon, François; Patel, Vinit; Männig, Max; Paschkewitz, John (MIT Sloan Management Review, 2023)
Deep tech involves applying emerging technologies to address big challenges — such as using mRNA technology to develop a COVID-19 vaccine. But taking advantage of deep tech can be a challenge for incumbent companies. The authors share a three-step framework to help leaders identify and execute their deep-tech engagement strategies. Using the European steel industry as an example, they describe the factors companies should consider when choosing an approach to deep tech in their own industries.